Resistensi Simbolik dan Aktivisme Digital: Analisis Fenomena Garuda Biru dalam Mengawal Demokrasi dan Konstitusi Indonesia - Ajeng Iva Dwi Febriana; Yadi Kusmayadi; Anton Ardiansyah (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
The planned ratification of the 2024 Regional Head Election Bill, which annulled the Constitutional Court's decision, triggered massive public resistance manifested through the "Blue Garuda Emergency Warning" symbol. This study analyzes the phenomenon using Christian Fuchs's Radical Humanism perspective and Jürgen Habermas's public sphere concept. Using a qualitative approach with a case study method, data were collected from social media platforms X and Instagram during the critical period of August 21-23, 2024. The research aims to dissect how visual symbols function as a medium of criticism amidst the stagnation of formal democratic channels. The findings show that the Blue Garuda is not merely a viral trend but an instrument of de-alienation that creates a counter-public sphere. Citizens engage in activism by transforming collective emotions into real political movements, both in the digital and physical realms. This phenomenon represents a social healing mechanism for the silencing of citizens' voices while marking a crisis of legitimacy for state institutions. The study concludes that Indonesia's digital democracy has evolved into a substantive corrective force, where nationalism is redefined as loyalty to the constitution and humanitarian values, not blind obedience to the authorities.